Shifting STEM Stereotypes? Considering the Role of Peer and Teacher Gender. (12th October 2016) - Riegle‐Crumb, Catherine; Moore, Chelsea; Buontempo, Jenny
Abstract : This study builds on research on the power of counter‐stereotypical cues, as well as intergroup contact theory, to consider whether interactions with a female teacher and female peers in a high school engineering classroom decrease male students' gender/science, technology, engineering, and math stereotypical beliefs and whether this varies according to the initial strength of their stereotypical views. Analyses reveal that among male students who initially reject stereotypes of male superiority, more female peers in the classroom leads to a further decrease in their stereotypical views by the end of the year. In contrast, boys who held strong stereotypical beliefs became less stereotypical by the end of the course when they had a female teacher. Implications for future research and current educational reforms are discussed.